Hubungan Pemberian ASI Eksklusif Dengan Kejadian Ispa Pada Balita Usia 7-24 Bulan Di Poskesdes Lemper Wilayah Kerja Puskesmas Pademawu - Riska Permana Sari; Kinanatul Qomariyah (Universitas Islam Madura, 2022)
Infancy and toddlerhood is a golden period for growth. Therefore, parents can be able to maximize the golden period. At the age of under 2 years, toddlers have a high infection rate because the antibodies formed have not been maximized. Based on a preliminary study, it was found that 50% of children under five had ARI, which was caused by mothers not exclusively breastfeeding. The purpose of this study was to determine the relationship between exclusive breastfeeding and the incidence of ARI in infants aged 7-24 months. This type of research is analytic correlation. Based on the time this research uses cross sectional. The independent variable is exclusive breastfeeding and the dependent variable is the incidence of ARI in infants aged 7-24 months. The population is 75 mothers who have toddlers aged 7-24 months at the Lemper Poskesdes Working Area of ​​the Pademawu Health Center, with a simple random sampling technique of 64 people. Data collection techniques using a questionnaire. Based on the cross tabulation, it shows that the mothers who did not give exclusive breastfeeding were 44 mothers, almost entirely 81.9% had ARI. From the statistical test of the chi square test using the SPSS 17 for windows program, with a value of = 0.05 and df = 1, the result is that X2 count (22.419) > X2 table (3.841) which means H0 is rejected and H1 is accepted and proven true, namely there is a relationship between exclusive breastfeeding and the incidence of ARI in toddlers aged 7-24 months at Poskesdes Lemper, Pademawu Community Health Center Work Area. Prevention efforts are the most strategic components to eradicate ARI, including fulfillment of nutrition, clean and healthy living habits, and exclusive breastfeeding. Exclusive breastfeeding for infants can avoid the risk of transmission of ISPA Keywords: exclusive breastfeeding, incidence of ISPA